Unillanos expands places in three undergraduate programs for the period 2024-2 (Contexto (Universidad de los Llanos), 2024)
In response to the needs of the academic offering in the region, the Universidad de los Llanos, through Academic Resolution No. 033 of 2024, established an increase of 144 places for the second period of the current year, which will be distributed as follows: 48 Systems Engineering students, 48 ​​places for the new Bachelor's program in Spanish and English and 48 places for the new Forestry Engineering program.As can be seen, the new places that our Institution has are destined for the programs with the highest demand among young applicants and the Systems Engineering program, one of the most attractive currently at Unillanos.
Keywords: academic offer; applicants; benefits; education